Controlling of Transformation Temperatures of Cu-Al-Mn Shape Memory Alloys by Chemical Composition - Canbay, C. Aksu; Karagoz, Z.; Yakuphanoğlu, Fahrettin (Polish Acad Sciences Inst Physics, 2014)
The Cu-Al-Mn shape memory alloys having various chemical compositions were prepared by arc melting method to control the phase transformation parameters. The phase transformation parameters and structural properties of the alloys were investigated by differential scanning calorimetry and optic microscopy, respectively. The effects of the chemical composition on characteristic transformation temperatures, enthalpy and entropy values of Cu-Al-Mn ternary system were investigated. The characteristic transformation temperatures of austenite and maxtensite phase (A(s), A(f), M-s, and M-f) are increased with change in the chemical composition of the alloys. The average crystallite size for the alloys was calculated to determine the effect of aluminum and manganese compositions on the transformation temperatures. The change in transformation temperatures indicates the same trend with change in crystallite size. The obtained results suggest that the phase transformation parameters of the Cu-Al-Mn alloys can be controlled by Al and Mn contents.
Keywords: Phase; Manganese